2018
DOI: 10.1039/c7nj02957h
|View full text |Cite
|
Sign up to set email alerts
|

Subphthalocyanine basicity: reversible protonation at the azomethine bridge

Abstract: International audienceSubphthalocyanine (SubPc) could be reversibly protonated at the azomethine bridge. This phenomenon was examined by addressing the pKa of the acid (TFA, MSA, TMSA) and the SubPc electron-withdrawing properties of the peripheral isoindolic substituents (F12 vs. H12 and NO2), which tunes the basic character of the azomethine moiety. The protonation of up to three azomethines was suggested and monitored spectrophotometrically with the appearance of new absorption bands at 610, 630 nm and 660 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Honda et al 36,37 has shown this for peripherally phenylated Pc derivatives. Our group 38 and Decreáu et al 39 have shown the same for boron subphthalocyanines. Therefore, the protonation and nitrogen atom loss are likely to be intimately associated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Honda et al 36,37 has shown this for peripherally phenylated Pc derivatives. Our group 38 and Decreáu et al 39 have shown the same for boron subphthalocyanines. Therefore, the protonation and nitrogen atom loss are likely to be intimately associated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In 19 F-NMR spectra of SubPc-F derivatives, a quartet centered between −160 and −155 ppm is originated by the axial fluorine substituent due to the coupling with the boron atom. 49,67,102,159…”
Section: Subphthalocyaninesmentioning
confidence: 99%
“…The appearance of the N–H and N–D stretching bands of the iminium species formed upon protonation and deuteration of the SubPc azomethine bridges was suggested by the authors as a possible rationale for this experimental finding. 67…”
Section: Subphthalocyaninesmentioning
confidence: 99%
See 2 more Smart Citations